Meaning of Pluralism for Indonesian Imigrant Workers in Malaysia - Prisgunanto, Ilham; Pranawukir, Iswahyu (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Workers always get bad reputation as marginal person in people. The critical problem for workers especially like no protection their rights from state in work place. Indonesian imigrant workers in Malaysia has bad image in any coverage press report. But in the other hand Indonesian imigrant workers be on the increase day by day in Malaysia, and they are able to adapted and interacted for their partners from other country in the workplace in Malaysia. All of this works because the Indonesian imigrant workers accept the pluralism in their workplace. This research talk about what the meaning of pluralism of Indonesian imigrant workers in Malaysia (mindset). Research uses convergency symbolic theory from Ernest Bormann which separate symbolic object for 3 factors likes; saga, self identity, and social interaction for other workers. The point of theoretical analysis get constructed the real social interaction Indonesian imigrant workers in Malaysia. Beside it, this research uses naration theory of Fisher De Aubrey which believe that grouping is the important aspect for humanbeing interaction. Paradigm of this research is constructivism, in qualitative model. Research interviews 14 persons Indonesian imigrant workers who had worked in Malaysia. Finding of research, Indonesian imigrant workers have special meaning for pluralism. For Indonesia imigrant workers Malaysia is a dream country, they do not hate that’s country so much. In Indonesian imigrant workers mind there is no pretension to make conflicts in their workplace. Over there work situations very busy and professionalism are completing work if talk about pluralism. Saga in this research find in success stories are so real because local lifestyle and culture of Indonesia and Malaysia are so similar. Construction pluralism for Indonesian workers so positive but they still love of their homeland, Indonesia.